2020
DOI: 10.4314/ijbcs.v14i5.18
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors determining ecosystem services local perceptions in two ecological zones in Benin (West Africa)

Abstract: Forests have been undergoing diverse threats due to human activities and these may affect their role as Ecosystem Services (ES) providers. Therefore, it becomes crucial to undertake some analysis of the current socio-economic context of ES offerings to provide valuable information for the decision-making process and policy regarding sustainable forest management. This study aimed at highlighting the local perception of ES in two contrasting ecological regions. 689 respondents distributed in six districts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…De son côté, la population locale prise dans l'ensemble ne reconnaît que le service de régulation et le service de support (formation de sols, développement du cycle nutritionnel, etc.). Ces observations rejoignent les résultats de nombreux auteurs qui ont mis en relief que la reconnaissance des services écosystémiques varie en fonction des répondants (Al-assaf et al, 2014 ;Garrido et al, 2017 ;Mensah et al, 2017 ;Ahononga et al, 2020). Par exemple, Garrido et al (2017) ont réalisé un inventaire des services écosystémiques fournis par les pâturages boisés de chênes de l'Ostergotland (Suède) tels qu'ils sont perçus par trois groupes de parties prenantes définies en fonction du secteur qu'elles représentaient, à savoir le secteur civil (comprenant les organisations non gouvernementales et les associations civiles), le secteur privé (comprenant les entreprises contrôlées ou détenues par des particuliers) et le secteur public (qui était représenté par des fonctionnaires gérant des intérêts publics par le biais d'agences gouvernementales et d'unités gouvernementales locales).…”
Section: Discussion Perception Des Services éCosystémiques Fournis Pa...unclassified
See 1 more Smart Citation
“…De son côté, la population locale prise dans l'ensemble ne reconnaît que le service de régulation et le service de support (formation de sols, développement du cycle nutritionnel, etc.). Ces observations rejoignent les résultats de nombreux auteurs qui ont mis en relief que la reconnaissance des services écosystémiques varie en fonction des répondants (Al-assaf et al, 2014 ;Garrido et al, 2017 ;Mensah et al, 2017 ;Ahononga et al, 2020). Par exemple, Garrido et al (2017) ont réalisé un inventaire des services écosystémiques fournis par les pâturages boisés de chênes de l'Ostergotland (Suède) tels qu'ils sont perçus par trois groupes de parties prenantes définies en fonction du secteur qu'elles représentaient, à savoir le secteur civil (comprenant les organisations non gouvernementales et les associations civiles), le secteur privé (comprenant les entreprises contrôlées ou détenues par des particuliers) et le secteur public (qui était représenté par des fonctionnaires gérant des intérêts publics par le biais d'agences gouvernementales et d'unités gouvernementales locales).…”
Section: Discussion Perception Des Services éCosystémiques Fournis Pa...unclassified
“…La reconnaissance de tous les types de services écosystémiques par les gestionnaires des aires protégées, constatée dans le cadre de la présente étude, résulterait du fait qu'en tant qu'acteurs les plus directement impliqués dans la conservation, ils seraient plus sensibilisés eu égard aux services écosystémiques offerts par les aires protégées comparativement à l'administration et la population. En effet, il est indiqué que la sensibilisation en matière de l'environnement joue un rôle important dans l'explication de la variation des perceptions des services écosystémiques (He et al, 2018 ;Bolanos-Valencia et al, 2019;Ahononga et al, 2020).…”
Section: Discussion Perception Des Services éCosystémiques Fournis Pa...unclassified
“…Indeed, the results of [35] indicate that the community in the Sudano-Guinean zone of Benin is mainly aware of regulatory services, namely those related to air quality and natural hazard regulation. Similarly, [36] showed that in the urban area of the city of N'djamena, 98.6% of the population planted trees for shade and coolness.…”
Section: Identification Of Types and Categories Of Ecosystem Services In The Citymentioning
confidence: 99%
“…These results show that the higher the level of education, the better the perception of ecosystem services. The level of instruction or education could induce people's attitude to support conservation policies and improve attitudes towards natural resources [38,39,40,41] cited by [35]. The characterization of ecosystem services according to socio-cultural groups in the city of Parakou revealed that Bariba and related people have a good knowledge of the provisioning, regulating and cultural services of the tree.…”
Section: Characterization Of Ecosystem Services By Social Groupsmentioning
confidence: 99%